Lithium-plasmon-based low-powered dynamic color display. Issue 1 (23rd June 2022) - Liang, Jie; Jin, Yan; Yu, Huiling; Chen, Xinjie; Zhou, Lin; Huo, Pengcheng; Zhang, Ye; Ma, Haiyang; Jiang, Yi; Zhu, Bin; Xu, Ting; Liu, Hui; et al.
ABSTRACT: Display and power supply have been two essential and independent cornerstones of modern electronics. Here, we report a lithium-plasmon-based low-powered dynamic color display with intrinsic dual functionality (plasmonic display and energy recycling unit) which is a result of the electric-field-driven transformation of nanostructured lithium metals. Dynamic color displays are enabled by plasmonic transformation through electrodeposition (electrostripping) of lithium metals during the charging (discharging) process, while the consumed energy for coloring can be retrieved in the inverse process respectively. Energy recycling of lithium metals brings energy consumption down to 0.390 mW cm −2 (0.105 mW cm −2 ) for the active (static) coloration state of a proof-of-concept display/battery device, which approaches nearly-zero-energy-consumption in the near-100%-energy-efficiency limit of commercial lithium batteries. Combining the subwavelength feature of plasmonics with effective energy recycling, the lithium-plasmon-based dynamic display offers a promising route towards next-generation integrated photonic devices, with the intriguing advantages of low energy consumption, a small footprint and high resolution. Abstract : Low-powered dynamic color display based on lithium-plasmon was for the first time reported with intrinsic dual-functions, the plasmonic display and energy recycling unit, through electric-driven transformation of nanostructured lithium metals.